Tinjauan Yuridis Sistem Perjanjian Pinjaman Online Berdasarkan Kitab Undang-Undang Hukum Perdata - Adela Pitri Yani Dewi; Taun Taun (Peneliti.net, 2023)
Online lending and borrowing agreements are transaction activities that continue to take place in people’s lives. So an online loan agreement is a type of ordinary loan agreement, but what distimguishes it is the intermediary media through online or online media. In the implementation of online loan agreements between debtors and creditors, it does not require space to interact directly. Online lending and borrowing agreements are considered legally valid because their provisions are still subject to articles 1320 and 1338 of the Civil Code. The benefits can be felt not only in the national scope but also in the world. As with the initial purpose of the internet being created as a means of connecting to make it easier for users to access everything they need, even now, the internet can also function as a medium for transaction. With the internet, the world’s economic development has significantly increased. This is due to the ease of convenience in transacting through internet technology media. In Article 1736 of the Civil Code, it is stated that whoever receives a loan, is obliged to return it in the same amount and condition, and at the specified time.